Complete Atrioventricular Block due to Infective Endocarditis of Bicuspid Aortic Valve - Park, Mi-Youn (Korean Society of Echocardiography, 2011)
A 38-year-old man visited our emergency department presenting with a 6-day persistent fever. The man had undergone an orthodontic procedure 7 days prior to the visit. He had a fever with a temperature of 38.2℃ and a diastolic murmur (grade III) was detected at the left sternal border. Reddish-brown lines beneath the nails were present, and raised lesions which were red and painful were detected on the soles of the patient's feet. Laboratory findings showed an elevated inflammatory marker. Transthoracic and transesophageal echocardiograms, showed a bicuspid aortic valve, and moderate aortic regurgitation and vegetation were noted. Treatment with antibiotics was given, but 4 days later, a 12 lead electrocardiogram revealed complete atrioventricular (AV) block. Immediately, a temporary pacemaker was inserted, and the following day an aortic valve replacement was performed. Intraoperative findings revealed a fistula around the AV node. He has suffered no subsequent cardiac events during the follow-up.